Evaluation of Business Model Canvas on Business Performance of Lampit MSMEs in Hulu Sungai Utara Regency - Setio Utomo; Saladin Ghalib; Irwansyah Irwansyah; M. Hasanur Arifin; Humaidi Humaidi; Farah Amalia; Rangga Novansyah; Adelia Citra Ifanka (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The purpose of this study is to evaluate the Business Model Canvas on Business Performance at Lampit MSMEs in Hulu Sungai Utara Regency. The purpose of this research activity is to test and evaluate the Business Model Canvas on Business Performance and evaluate the Business Model Canvas on Lampit MSMEs in the Wetland Area of ​​Hulu Sungai Utara Regency. The model produced in this study is expected to be able to contribute to improving Lampit MSMEs in Hulu Sungai Utara Regency. The methods used are quantitative and qualitative. Quantitative research aims to test to determine the value of independent variables, either one or more variables (independent) without making comparisons, or connecting with other variables. While Qualitative aims to describe/construct in-depth interviews with research subjects so that they can provide a clear picture of the Business Model Canvas analysis in improving business performance at Lampit MSMEs in Hulu Sungai Utara Regency. The results of data processing using the Partial Least Square analysis model using the SmartPLS computer program, obtained the results that the Business Model Canvas (Customer Segment, Customer Relationship, Customer Channel, Revenue Structure, Value Proposition, Key Activities, Key Resources, Cost Structure, and Key Partners) has an effect on the business performance of Lampit MSMEs, while the results using SWOT analysis show that Lampit MSMEs have indirectly implemented the Business Model Canvas concept in carrying out their business and the application of the Business Model Canvas to Lampit MSME Products can help Lampit MSMEs survive and develop Keywords: Business Model Canvas, Business Performance, SWOT